LEGAL POLITICS OF POSTPONING THE REGIONAL HEAD ELECTIONS IN ACEH FROM 2022 TO 2024 - Asrina, Suci; Yusrizal, Yusrizal; Mukhlis, Mukhlis (Program Studi Magister Hukum Universitas Malikussaleh, 2024)
This study aims to examine the legal politics of postponing the regional elections from 2022 to 2024, and to analyze the implications of postponing the regional elections in Aceh in connection with Aceh's special status. The legal politics in Aceh in the implementation of the regional elections, which were supposed to be held in 2022 but have been moved to 2024, were previously considered a special authority of Aceh as regulated in the Regional Autonomy Law (UUPA), but in its development, it must comply with and follow the rules of the national regional elections. This research is a normative legal research with a legislative approach, case approach, and concept approach, data is obtained through primary, secondary, and tertiary data and will be analyzed, then the research results will be systematically arranged to obtain clarity from the problems being studied. Based on the research results, the legal politics of postponing the Aceh regional elections is the implementation of Article 201 paragraph (8) and Article 199 of Law No. 10/2016, as well as the KPU Circular Letter, viewed from the political configuration can be categorized as an orthodox political configuration, the implication of the postponement of the regional elections is due to the presence of Article 199 of the Regional Election Law and in the Constitutional Court's decision to cancel the implementation of the Aceh Regional Elections regulated in the UUPA.